Global Current Account Imbalances: American Fiscal Policy versus East Asian Savings - Chinn, Menzie D.; Ito, Hiro (My University, 2007)
The authors consider the origins of global current account imbalances and find that for industrial countries, the government budget balance is an important determinant of the current account balance. Their estimates lead them to conclude that fiscal factors might be as important as excess savings arising from East Asia.